2014
DOI: 10.1109/tim.2014.2323137
|View full text |Cite
|
Sign up to set email alerts
|

A Fast and Accurate PMU Algorithm for P+M Class Measurement of Synchrophasor and Frequency

Abstract: The IEEE Standard C37.118.1 defines two performance classes, P and M, for phasor measurement units (PMUs), respectively for protection and monitoring oriented applications. The goal of this paper is to define an algorithm that allows the requirements of both classes to be met simultaneously, thus avoiding an a priori selection of either the fast response time of class P or the accuracy of the class M. The designed PMU consists of two digital channels that process in parallel the acquired samples with different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
84
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(84 citation statements)
references
References 18 publications
0
84
0
Order By: Relevance
“…Recently, the idea of a single PMU capable of satisfying both the P and M-class PMU requirements at the same time has become increasingly popular [4], [5]. The advantages are evident: from a cost perspective, an electrical utility interested to use PMUs to simultaneously supply monitoring…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the idea of a single PMU capable of satisfying both the P and M-class PMU requirements at the same time has become increasingly popular [4], [5]. The advantages are evident: from a cost perspective, an electrical utility interested to use PMUs to simultaneously supply monitoring…”
Section: Introductionmentioning
confidence: 99%
“…The technique self-switches from an M-class algorithm to a P-class one in case a transient event is detected. On the contrary, [5] proposes a two-channel design that is conceived to comply with P and M-class at once. The process implements in parallel two different Taylor Fourier Transform algorithms, not designed to meet P and M-class respectively: the first one produces accurate measurements of steady state signals, while the second one is better suited to follow fast signal changes.…”
Section: Introductionmentioning
confidence: 99%
“…In the TWLS algorithm the analyzed waveform is apriori weighted by a suitable window [7], [8] and the nominal frequency is used as reference frequency in the adopted waveform model [8]. Recently, it has been shown that more accurate phasor, frequency, and ROCOF estimates can be achieved when the reference frequency coincides with the true waveform frequency [14]. In particular, raw discretization of the allowed reference frequency range has been proposed in order to evaluate a-priori the matrix employed by the TWLS estimator, which considerably reduces the required processing effort.…”
Section: Introductionmentioning
confidence: 99%
“…It is apparent that the error ranges are well under the bounds of the standard [1]. A good tabular summary of the standard bounds for the test signals can also be found in [28]. Furthermore, the obtained results improve those comparable in [10], with smaller TVE and shorter transient tails.…”
Section: Discussionmentioning
confidence: 55%